Yard cleaner / Aiman Haziq Ahmad Hashni and Haszeme Abu Kasim - Hashni Ahmad, Aiman Haziq; Abu Kasim, Haszeme (School of Mechanical Engineering, 2023)
The goal of this project is to facilitate the efficient cleaning and disposal of debris using a raking process. Traditionally, workers have had to manually collect cut grass and other debris by hand, which can result in dirty hands and require them to repeatedly bend over. This project aims to make the cleaning process easier and more accessible for workers, especially older individuals. The proposed solution involves a pulley system that incorporates a switch, DC motor, sprockets, shafts, chains, and rakes. By simply pressing a switch button, workers can activate the chain and rake mechanism to efficiently gather the cut grass. The hope is that this project will not only improve cleaning efficiency but also contribute to the health and well-being of workers, including older individuals and housewives, who would otherwise experience physical strain and discomfort during the cleaning process.